High-Tg Thiol-Click Thermoset Networks via the Thiol-Maleimide Michael Addition - Parker, Shelbi; Reit, Radu; Abitz, Haley; Ellson, Gregory; Yang, Kejia; Lund, Benjamin; Voit, Walter E. (Macromolecular rapid communications., 2016)
Thiol‐click reactions lead to polymeric materials with a wide range of interesting mechanical, electrical, and optical properties. However, this reaction mechanism typically results in bulk materials with a low glass transition temperature (Tg) due to rotational flexibility around the thioether linkages found in networks such as thiol‐ene, thiol‐epoxy, and thiol‐acrylate systems. This report explores the thiol‐maleimide reaction utilized for the first time as a solvent‐free reaction system to synthesize high‐Tg thermosetting networks. Through thermomechanical characterization via dynamic mechanical analysis, the homogeneity and Tgs of thiol‐maleimide networks are compared to similarly structured thiol‐ene and thiol‐epoxy networks. While preliminary data show more heterogeneous networks for thiol‐maleimide systems, bulk materials exhibit Tgs 80 °C higher than other thiol‐click systems explored herein. Finally, hollow tubes are synthesized using each thiol‐click reaction mechanism and employed in low‐ and high‐temperature environments, demonstrating the ability to withstand a compressive radial 100 N deformation at 100 °C wherein other thiol‐click systems fail mechanically. The thiol‐maleimide Michael addition is demonstrated as a reaction mechanism used to synthesize high‐Tg thiol‐click thermosetting networks that exhibit Tgs 80 °C higher than similarly structured thiol‐click systems. Hollow cylindrical samples of each composition are fabricated and loaded radially, showing the thiol‐maleimide thermosets withstanding a 100 N load at elevated temperatures.